Iberia : Spanish travels and reflections - Michener, James A. (Corgi, 1971)
Volume 1: Contains chapters on Badajoz, Toledo, Cordoba, Las Marismas, Sevilla and Madrid. - - Volume 2: Contains chapters on Salamaca, Pamplona, Barcelona, The Bulls, Turuel & Santaigo de Compostella.